The Netherlands: Old Emigrants - Young Immigrant Country - Jan C. van Ours; Justus Veenman (Institute for the Study of Labor (IZA), 1999)
Since the mid 1960s the Netherlands has an immigration surplus, mainly because of manpower recruitment from Turkey and Morocco and because of immigration from the former Dutch colony of Surinam. Immigrant workers have a weak labour market position, which is mainly related to their educational level and language skills. Children and grandchildren of immigrants are expected to have better chances to integrate into Dutch society. Nevertheless, specific policy measures are needed to avoid social exclusion of current immigrant workers.
Keywords: J61; J15; 330; Immigration; ethnic minorities; immigrant workers; Internationale Wanderung; Ausländische Arbeitskräfte; Soziale Integration; Niederlande